Secondhand Smoke Exposure During Pregnancy and Mothers’ Subsequent Breastfeeding Outcomes: A Systematic Review and Meta-Analysis - Daichi Suzuki (Nature Portfolio, 2019)
Abstract Secondhand smoke exposure of non-smoking women during pregnancy is associated with a higher risk of adverse birth outcomes. However, the available evidence regarding the association between expectant mothers’ secondhand smoke exposure and breastfeeding outcomes remains limited. This systematic review aimed to examine associations between secondhand smoke exposure of nonsmoking women during pregnancy with the initiation, prevalence, and duration or breastfeeding compared to women who were breastfeeding and had not been exposed to secondhand smoke. Women who smoked during pregnancy were excluded. We included case-control, cross-sectional, and cohort studies with a comparison control group. Medline CINAHL, and EMBASE were searched in January 2017. After screening 2777 records we included eight prospective cohort studies. The risk of bias assessment tool for non-randomized studies indicated a high risk of outcome assessment blinding. Meta-analysis of two studies established that the odds of discontinuation of any brestfeeding before six months were significantly increased in the secondhand smoke exposed women (pooled odds = 1.07 [95%CI = 1.01, 1.14], two studies, 1382 women). Therefore, secondhand smoke might be associated with discontinuing any breastfeeding before six months. More research is necessary to understand the association between secondhand smoke and the initiation, prevalence and duration of breastfeeding.